Growth dynamics of cancer cell colonies and their comparison with noncancerous cells - Huergo, María Ana Cristina (2012)
The two-dimensional (2D) growth dynamics of HeLa (cervix cancer) cell colonies was studied following both their growth front and the pattern morphology evolutions utilizing large population colonies exhibiting linearly and radially spreading fronts. In both cases, the colony profile fractal dimension was df = 1.20 ± 0.05 and the growth fronts displaced at the constant velocity 0.90 ± 0.05 μm min−1. Colonies showed changes in both cell morphology and average size. As time increased, the formation of large cells at the colony front was observed. Accordingly, the heterogeneity of the colony increased and local driving forces that set in began to influence the dynamics of the colony front. The dynamic scaling analysis of rough colony fronts resulted in a roughness exponent α = 0.50 ± 0.05, a growth exponent β = 0.32 ± 0.04, and a dynamic exponent z = 1.5 ± 0.2. The validity of this set of scaling exponents extended from a lower cutoff lc ≈ 60 μm upward, and the exponents agreed with those predicted by the standard Kardar-Parisi-Zhang continuous equation. HeLa data were compared with those previously reported for Vero cell colonies. The value of df and the Kardar-Parisi-Zhang-type 2D front growth dynamics were similar for colonies of both cell lines. This indicates that the cell colony growth dynamics is independent of the genetic background and the tumorigenic nature of the cells. However, one can distinguish some differences between both cell lines during the growth of colonies that may result from specific cooperative effects and the nature of each biosystem.